One Day in the Life of Rufus Wainwright - Hailand, Tim (Hailand Books, 2010)
One Day in the Life of Rufus Wainwright follows the singer-songwriter from New York City to Boston for his performance at the Boston Opera House, which featured his sister Martha Wainwright as a special guest. With an intro by NYC nightlife legend Cherry Vanilla and text from Rufus himself.